Ion-plasma nitriding of titanium alloys: technologies, advantages, and limitations. - Rakhadilov, B.K.; Magazov, N.M.; Uazyrkhanova, G.K.; Aringozhina, Z.E.; Uazyrkhanova, Z.K.; Askhatov, A.N. (Recent Contributions to Physics, 2025)
To improve the surface properties of titanium and its alloys, numerous surface modification processes have been developed through the formation of coatings, films, or layers. One such treatment method is plasma nitriding, which is widely used to enhance the surface properties of titanium and its alloys. The diffusion of nitrogen into the bulk material creates a continuous hardness profile, thereby providing optimal support for the hard surface layer. This study examines the ion-plasma nitriding technology for the treatment of titanium alloys. The fundamental principles of ion-plasma nitriding, its advantages, and limitations are thoroughly analyzed, and the optimal process parameters that contribute to increasing the wear resistance and durability of titanium alloys are identified. The study includes an analysis of modern approaches and trends in the development of this technology, allowing for the identification of the most efficient processing modes and improvements in the characteristics of the resulting layers. Special attention is given to the influence of processing parameters such as temperature, pressure, gas mixture composition, and exposure time on the formation of the structure and properties of the nitrided layers. Research has shown that properly selected processing modes not only increase the microhardness and wear resistance of the surface but also reduce the coefficient of friction, which is particularly important for components operating under high mechanical loads. In addition, ion-plasma nitriding is compared with other surface modification methods for titanium, such as gas nitriding, laser hardening, and the application of hard coatings. The key advantages of this method have been identified, including the high uniformity of the nitrided layer, minimal dimensional changes in the components, and the environmental safety of the process. The obtained results can be used to optimize industrial processing technologies for titanium alloys, enabling their expanded application in the aerospace, medical, and mechanical engineering industries, where high reliability and durability of materials are required.